Structural Change in Europe During the Crisis - Peter Havlik (FIW - Research Centre International Economics, 2014)
This note examines the extent and patterns of structural changes that have occurred in European economies during the recent crisis using some stylised facts on changing output and employment struc-tures at detailed sectoral level. Focusing mainly on the new EU member states, we compare the perform-ance of various European countries by looking at the differentiated impact of the recent crisis on struc-tural shifts in their economy. We start with stylised facts related to output and employment structures at broader sectoral (NACE-2) level and attempt to find out whether there has been a structural convergence (or divergence) of the New EU Member States (NMS) compared to the more advanced old' EU countries (OMS) during the crisis. Finally, we provide also some policy conclusions related to the future role of the NMS in the economy of an integrated Europe, especially in view of post-crisis growth challenges. The fi-nancial crisis 2008-2011 adversely affected manufacturing industry more than services - particularly in terms of employment - and accelerated structural change in favour of the services sector. The latter ten-dency was more pronounced in the NMS though even here country specific differences were remarkable. The importance of industry in this group of countries remains strong. There has been no EU-wide uniform pattern of structural change; the formulation of industrial policy at EU level - even reaching the 20% target of industry's share in GDP - is challenging and hardly attainable.
Keywords: L13; L52; J3; 330; Industry; structural change; European economy; growth; crisis